2013
DOI: 10.1159/000349980
|View full text |Cite
|
Sign up to set email alerts
|

Oral, Esophageal and Cutaneous Lichen Ruber Planus Controlled with Alitretinoin: Case Report and Review of the Literature

Abstract: Background: Therapy-resistant lichen planus (LP) can be a challenging condition for dermatologists. There are some case reports about successful treatments with alitretinoin of cutaneous and oral, but not of esophageal LP. Objective: We present the unique case of a patient with cutaneous, oral and esophageal LP which was refractory to classical treatment options (topical clobetasol propionate and pimecrolimus, intramuscular triamcinolone acetonide); because of systemic side effects the patient did not tolerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 112 publications
0
23
0
4
Order By: Relevance
“…In addition to its approved use, alitretinoin has been reported to be beneficial also in refractory pityriasis rubra pilaris [6] , lichen planus [7,8] , cutaneous lupus erythematosus [9] , palmoplantar pustular psoriasis [10] as well as in mycosis fungoides [11] , but it appeared to have a mixed effect in congenital ichthyosis [12] . Several studies have also been carried out with alitretinoin used in the treatment of AIDS-related Kaposi's sarcoma [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its approved use, alitretinoin has been reported to be beneficial also in refractory pityriasis rubra pilaris [6] , lichen planus [7,8] , cutaneous lupus erythematosus [9] , palmoplantar pustular psoriasis [10] as well as in mycosis fungoides [11] , but it appeared to have a mixed effect in congenital ichthyosis [12] . Several studies have also been carried out with alitretinoin used in the treatment of AIDS-related Kaposi's sarcoma [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of systemic retinoids for LP is supposed to result from their antiproliferative mode of action mediated by binding to nuclear receptors (RAR and RXR) and there is some evidence of receptor expression in the nail matrix [4]. The positive effect of alitre- tinoin on skin, oral, esophageal and nail LP has already been described [5]. In our 2 cases, the patients showed nail LP which was refractory to classic treatment options (topical corticosteroid and tacrolimus ointment 0.1%).…”
Section: Discussionmentioning
confidence: 99%
“…We report 2 cases of nail LP that were successfully treated with alitretinoin. Using PubMed, a review of the English literature revealed one case report of nail LP treated with alitretinoin [4] and another case of oral, esophageal and cutaneous LP controlled with alitretinoin that also showed nail improvement [5]. Our objective is to report additional cases to the scant existing literature to learn more about therapeutic options for nail LP.…”
Section: Introductionmentioning
confidence: 99%
“…In one anecdotal report, a patient was treated with 30 mg/day with good results within 4 weeks. No severe side effects were registered, but oral striae and dysphagia recurred during treatment and LP relapsed after 4 months (Kolios et al 2013 ).…”
Section: Retinoidsmentioning
confidence: 93%
“…Recently, some reports of recalcitrant lichen planus successfully treated with alitretinoin have been published (Kolios et al 2013 ;Brehmer et al 2011 ).…”
Section: Retinoidsmentioning
confidence: 99%